Manajerialisasi Dana Pihak Ketiga terhadap Peningkatan Laba Operasional Pada PT (Persero) Bank Jabar Syariah Bandung - Teddy Hikmat Fauzi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Based on the data collected from the result of the study, it shown that the influence of third party deposit on the operational profit in PT. Bank Jabar Syariah Branch Bandung, according to Product Moment the correlation coefficien yielded is 0,93 and the critical point tabel T for N=5 is 2,353, then the hypothesis testing drawn out is 4,382 > its 2,353 which means that between third party deposit and operational profit has significant correlation. Furthemore the determination coefficient yielded is 86% to the operational profit. This shows that third party deposit have correlation up 86% to the operational profit. The rest 14% is the other variables apart from the activity of third party deposit which influencing the operational profit in PT. Bank Jabar Syariah Branch Bandung. The stumbling blocks that the PT Bank Jabar Syariah Branch Bandung in management of third party deposit to acquirement operational profit that is existence of emulation from competitor bank either from interest rate facet, marketing, product diversivication and also service. Condition of less stable economic sector, happened of management miss between mustered fund and channelled fund.The recommendation the Researcher can give are the company should more accurate do deposit management for time deposit and the company should do cooperate with another Bank, not only for ATM served but also company should do cooperate in technology to be individual wealth banking to served otherwise as like SMS-Banking, Internet-Banking, etc. so that income not only for the greater part spread based income but also from fee based income.Keywords: Fund, Bank Management, profit